2023
DOI: 10.3390/app13042118
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Plant-Based Foods and Intense Physical Activity on the Metabolic Health of Women with PCOS: A Priori Dietary-Lifestyle Patterns Approach

Abstract: The study aimed to analyse dietary-lifestyle patterns (DLPs) and their relation with visceral obesity and other metabolic parameters in women with PCOS. A total of 140 women were diagnosed with PCOS. The KomPAN® and The ShortIPAQ questionnaires analysed the food frequency intake, health habits, economic situation, and physical activity. The dual-energy-x-ray absorptiometry (DXA) measured the visceral and total adipose tissue. The analysis distinguished three DLPs: western (WDLP), prudent (PDLP) and active (ADL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…The Mediterranean diet, DASH diet (Dietary Approaches to Stop Hypertension) and low glycemic index diet seem to be the healthiest dietary approaches that have the strongest relationship with greater insulin sensitivity among PCOS women [12][13][14][15]. A study by Bykowska-Derda et al [3] showed that PCOS women with low adherence to the western dietary pattern were at a lower risk of having IR. In particular, high intake of meat was associated with metabolic disorders in PCOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mediterranean diet, DASH diet (Dietary Approaches to Stop Hypertension) and low glycemic index diet seem to be the healthiest dietary approaches that have the strongest relationship with greater insulin sensitivity among PCOS women [12][13][14][15]. A study by Bykowska-Derda et al [3] showed that PCOS women with low adherence to the western dietary pattern were at a lower risk of having IR. In particular, high intake of meat was associated with metabolic disorders in PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the excessive accumulation of the visceral adipose tissue is also reported in PCOS women with normal body weight; thus, this parameter is not only related to BMI (body mass index). In addition, such fat distribution is strongly linked to hyperglycemia, compensatory hyperinsulinemia and insulin resistance [3,4]. Moreover, the adipose tissue is a very crucial and active endocrine organ which synthesizes and secretes a variety of adipokines influencing the regulation of metabolism related to the sensitivity of tissues to insulin [5].…”
Section: Introductionmentioning
confidence: 99%
“…Principal component analysis (PCA) was used to isolate dietary patterns (DPs). The dietary patterns were identified by considering the following criteria: (1) the eigenvalues of the variable correlations >1.0, (2) the plot of the eigenvalues, and (3) the total explained variance [49]. Rotated factor loadings with an absolute value of |0.50| were considered to be specific to the pattern [49].…”
Section: Discussionmentioning
confidence: 99%
“…The dietary patterns were identified by considering the following criteria: (1) the eigenvalues of the variable correlations >1.0, (2) the plot of the eigenvalues, and (3) the total explained variance [49]. Rotated factor loadings with an absolute value of |0.50| were considered to be specific to the pattern [49]. For each patient and each pattern, the scores were calculated as a product of the factor loading and food frequency consumption [49].…”
Section: Discussionmentioning
confidence: 99%
“…11 However, a range of dietary patterns underpinned by general healthy eating principles are beneficial for PCOS management, independent of weight change. 51,52 The benefits are potentially due to the effects on the chronic low-grade inflammatory environment of PCOS, which is mediated by higher fat mass, insulin resistance, and high androgen concentration. 53 For example, the Mediterranean Diet (MedDiet) has been found to be beneficial in PCOS populations, 20,54,55 as it reduces inflammatory markers, testosterone, and Ferriman-Gallwey score and improves insulin resistance and hyperandrogenemia.…”
Section: Lifestyle Intervention: Important With or Without Medical Th...mentioning
confidence: 99%